A narrative review of spermbots in assisted reproduction: Integrating AI for enhanced fertility outcomes and future innovations - Neeraj Vishwakarma; Nancy Nair; Charu Pareek; Namrata Choudhary (Asian Pacific Journal of Reproduction, 2025)
Sperm-structure-integrating nanodecorated microrobots have shown promise in medicine delivery and infertility treatment. A variety of spermbots use cutting-edge nanomaterials and 3D printing technology to enhance their functioning, such as biomimetic sperms and flagellate microorganisms. The success rates of assisted reproductive technology techniques like in vitro fertilisation (IVF) and intracytoplasmic sperm injection (ICSI) may increase as a result of these developments. Furthermore, the incorporation of artificial intelligence (AI) into spermbots has the potential to optimize reproductive therapies by reducing inherited illnesses through genetic screening and editing. However, before the widespread implementation of spermbots in clinical practice, several critical aspects must be addressed. Thorough investigations into biocompatibility, ethical considerations, and long-term safety are necessary to ensure that these technologies are safe and effective for in vivo applications.